2022
DOI: 10.1038/s41392-022-00955-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and atherosclerosis: signaling pathways and therapeutic intervention

Abstract: Atherosclerosis is a chronic inflammatory vascular disease driven by traditional and nontraditional risk factors. Genome-wide association combined with clonal lineage tracing and clinical trials have demonstrated that innate and adaptive immune responses can promote or quell atherosclerosis. Several signaling pathways, that are associated with the inflammatory response, have been implicated within atherosclerosis such as NLRP3 inflammasome, toll-like receptors, proprotein convertase subtilisin/kexin type 9, No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(239 citation statements)
references
References 383 publications
(354 reference statements)
2
173
0
Order By: Relevance
“…Of note, statins upregulate LDLR through sterol regulatory binding protein-2, which also enhance the expression of PCSK9. Accumulating evidence have demonstrated that PCSK9 induces the formation of LDLR-PCSK9 complex, leading to the degradation of LDLR in lysosomes, thereby reducing LDLR recycling and LDL-P clearance ( Guo et al, 2020 ; Kong et al, 2022 ).…”
Section: Therapies Targeting Ldl-pmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, statins upregulate LDLR through sterol regulatory binding protein-2, which also enhance the expression of PCSK9. Accumulating evidence have demonstrated that PCSK9 induces the formation of LDLR-PCSK9 complex, leading to the degradation of LDLR in lysosomes, thereby reducing LDLR recycling and LDL-P clearance ( Guo et al, 2020 ; Kong et al, 2022 ).…”
Section: Therapies Targeting Ldl-pmentioning
confidence: 99%
“…The pathological basis of CVD is atherosclerosis, a disease of arteries causing myocardial infarction, stroke, and other complications ( Libby et al, 2019 ). Atherosclerosis occurs primarily in the subendothelial space of the middle and large arteries, where blood flow is disturbed and/or bifurcated ( Siasos et al, 2018 ; Kong et al, 2022 ). Accumulating evidence have demonstrated that many risk factors including hyperlipidemia, hypertension, oxidative stress, inflammation, endothelium dysfunction as well as high-calorie diet and unhealthy habits, such as smoking, contribute to the initiation and progression of atherosclerotic CVD (ASCVD) ( Lee and Cooke, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, neoastilbin inhibited GA, including inflammatory cytokine release and inflammatory cell infiltration into the lesion site, mediated by the suppression of NF-κB and NLRP3 inflammasome pathways in THP-1-derived macrophages and GA mice. Considering that the NF-κB and NLRP3 inflammasome pathways are related to the development of many inflammatory diseases, neoastilbin may have potential clinical application value in gout, autoinflammatory syndrome or other NLRP3-driven diseases [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Locally, lipid accumulation leads to free radical formation, endothelial activation and inflammation, all resulting in an imbalance in reactive oxygen species, which transform monocytes into foam cells [ 75 ]. This process involves multiple cell types, both intracellular and extracellular reactive oxygen and nitrogen species and complex signalling pathways, including the NLRP3 inflammasome pathway, the Wnt and Notch pathways, Toll-like receptors and proprotein convertase subtilisin/kexin type 9 [ 75 , 76 ]. Systemic biomarkers of inflammation, such as high-sensitivity C-reactive protein and interleukin-6, are both associated with risk of ACS [ 77 ].…”
Section: High-risk Plaque Featuresmentioning
confidence: 99%